Beiträge zur Insektenfauna der DDR: Gattung Carabus Linné (Coleoptera: Carabidae). - Arndt, Erik (Contributions to Entomology = Beiträge zur Entomologie, 1989)
From the GDR 23 species of genus Carabus L. (Col., Carab.) are known. The presence of one species (Carabus variolosus F.) is doubtful, it was found in 1843 only. Two species (C. marginalis F. and C. menetriesi Hummel) are glacial relics and very rare at present. 10 species were found at least in 14 (of 15) districts recently. The most common and distict adaptablest species are C. nemoralis Mueller and C. granulatus L.